Trace element partitioning between pyrochlore, microlite, fersmite and silicate melts - Stephan Klemme; Jasper Berndt (Geochemical Transactions, 2020)
Abstract We present experimentally determined trace element partition coefficients (D) between pyrochlore-group minerals (Ca2(Nb,Ta)2O6(O,F)), Ca fersmite (CaNb2O6), and silicate melts. Our data indicate that pyrochlores and fersmite are able to strongly fractionate trace elements during the evolution of SiO2-undersaturated magmas. Pyrochlore efficiently fractionates Zr and Hf from Nb and Ta, with DZr and DHf below or equal to unity, and DNb and DTa significantly above unity. We find that DTa pyrochlore-group mineral/silicate melt is always higher than DNb, which agrees with the HFSE partitioning of all other Ti–rich minerals such as perovskite, rutile, ilmenite or Fe-Ti spinel. Our experimental partition coefficients also show that, under oxidizing conditions, DTh is higher than corresponding DU and this implies that pyrochlore-group minerals may fractionate U and Th in silicate magmas. The rare earth element (REE) partition coefficients are around unity, only the light REE are compatible in pyrochlore-group minerals, which explains the high rare earth element concentrations in naturally occurring magmatic pyrochlores.